The Role of Energy Storage in Climate Change Mitigation: Engineering Solutions for Enhancing Renewable Energy Integration - Nursahar Buang; Sara Hussain; Harizahayu Harizahayu (Yayasan Adra Karima Hubbi, 2026)
Background. Climate change mitigation remains a pressing global challenge, with renewable energy adoption emerging as a critical strategy to reduce greenhouse gas emissions. However, the intermittent nature of renewable sources such as solar and wind limits their effectiveness and reliability in energy supply. Energy storage systems have the potential to address these challenges by stabilizing power output, enhancing grid resilience, and enabling more extensive integration of renewable resources. Purpose. This study aims to investigate the role of engineering solutions in energy storage for supporting renewable energy integration and advancing climate change mitigation goals. Method. A mixed-methods approach was employed, combining literature review, technical performance analysis, and comparative case studies of energy storage technologies including batteries, pumped hydro, and thermal storage systems. Data were collected on system efficiency, storage capacity, scalability, and deployment outcomes in diverse energy networks. Results. Results indicate that energy storage significantly improves renewable energy utilization, reduces curtailment, and contributes to grid stability. Advanced battery technologies and hybrid storage systems demonstrated the highest potential for large-scale integration, while engineering optimization enhanced system efficiency and reliability. Conclusion. The study concludes that integrating energy storage solutions is essential for effective climate change mitigation, providing both technical and strategic pathways to accelerate renewable energy adoption and enhance sustainable energy infrastructure.